Penciptaan Wirausaha Baru di Kampus Poltekkes Kemenkes Palu melalui Pengembangan Produk-Produk Bakery dan Kudapan - Nurjaya, Nurjaya; Aminuddin, Aminuddin; Bahja, Bahja (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The liver and entrails of cakalang fish can be mixed into bakery products and other snacks using the latest technology to eliminate the fishy flavours. Although this product is believed to have selling value, this product has never been used as an idea in entrepreneurship. the target group is students and graduates who are or have been in the product sales business and have experience in the field of product marketing, a total of 10 people. The method of implementing the coaching system is related to practical knowledge about entrepreneurship and product manufacturing through training activities and technical guidance. Monitoring and evaluation of program success is carried out after 3 (three) months of entrepreneurial development with the achievement targets being the number of promotional activities and net profit earned. The results obtained were that there were 4 (four) people or 40% of participants who developed products in their line of business, where 2 people carried out business/entrepreneurship development and 2 people developed products into a snack menu at work. The average percentage of sales profit achievement is around 50% calculated during product sales. Based on the results of the program, it can be concluded that superior products have been created that can be developed into business ventures for students and graduates as training participants.